2022
DOI: 10.3390/plants11192535
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and Floral Biology of Diospyros sericea A. DC. (Ebenaceae): Inconstant Males May Be behind an Enigma of Dioecy

Abstract: Diospyros sericea is a tree/shrub species considered dioecious and broadly distributed in Brazil. Despite its importance for niche composition in a range of ecosystems, there is little knowledge about this species, and so far no study has analyzed its sexual system. We aimed to investigate dioecy expression in D. sericea through sexual dimorphisms in its phenology and floral biology. We analyzed the phenological events over a year and studied floral biology traits (morphology, flower development, floral resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…(Rubiaceae) and found that although the species has nocturnal flowers, the flowers remain open into the early morning, which allows for the plant to play host to a larger arthropod community. Ramalde et al [ 14 ] explored dioecy in Diospyros sericea A.DC. (Ebenaceae), and these authors not only recognized vestigial sexual organs in the unisexual flowers but also identified some plants as being sexually leaky, with plants that develop staminate flowers also producing some fruits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Rubiaceae) and found that although the species has nocturnal flowers, the flowers remain open into the early morning, which allows for the plant to play host to a larger arthropod community. Ramalde et al [ 14 ] explored dioecy in Diospyros sericea A.DC. (Ebenaceae), and these authors not only recognized vestigial sexual organs in the unisexual flowers but also identified some plants as being sexually leaky, with plants that develop staminate flowers also producing some fruits.…”
mentioning
confidence: 99%
“…Additionally, and possibly more importantly, these studies demonstrate that it is crucial to take a closer look at supposedly understood biological phenomena. For example, Ramaldes et al [ 14 ] recognized fruit development on staminate plants of the dioecious D. sericea ; Pimienta and Koptur [ 13 ] identified new floral visitors for G. scabra given that the plants were open during dawn, not just at night; Johnson et al [ 16 ] recognized seed herbivory as a potential limiting factor in the success of M. alba ; and Kolarčik et al [ 17 ] found the critical role rare reproductive events play in maintaining species. These studies on plant breeding systems should serve as a reminder to botanists and conservation biologists of the important role of careful field observations.…”
mentioning
confidence: 99%